Nature and Self-Regulated Synthesis of the Repressor of the hut Operons in Salmonella typhimurium - Smith, Gerald R. (1971)
The enzymes mediating histidine utilization, coded by the hut genes, in Salmonella typhimurium are synthesized from two closely-linked operons. Results presented in this paper show that these operons are regulated by a single repressor protein. The hutC gene, coding for this repressor, is part of one of the operons. Since this same operon is sensitive to the repressor, the repressor apparently represses its own synthesis.